Assistência estudantil na UFPA: o estado da arte - RIBEIRO, Drielle Lucia Gomes da Silva (2021)
This article presents the qualitative approach research carried out through the State of the Art in the year 2017. The objective was to analyze the theoretical productions developed at the Federal University of Pará on the Student Assistance Policy to identify which aspects have been privileged on the PNAES in this context. The theoretical productions were searched from April to October 2017 on the Scielo, Google Academic, Capes Bank of Theses, UFPA Virtual Library Database and UFPA Physical Library Database, Campus Altamira, by means of the descriptors "Program of Student Assistance in UFPA", "PNAES in UFPA" and "Permanency Program in UFPA". The criterion for inclusion in the analytical corpus was to investigate the PNAES and to have been published in the period from 2007 to 2017. Sixty-one productions were identified, of which 11 were composed of the analytical corpus. It was identified that the theoretical productions on the PNAES in the UFPA are incipient. In general, in the studies, discussions are proposed on aspects related to the need to implement actions related to student assistance in order to contribute to the student's permanence in higher education, and point out limitations and weaknesses in relation to the implementation of these policies, mainly in the interior campuses on which did not identify productions that problematized student assistance indicating a gap in this discussion and a field for further research.